1984
DOI: 10.1111/j.1469-8749.1984.tb04447.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Congenital Optic Nerve Hvpoplasia: Review of 51 Patients

Abstract: Fifty-one patients with congenital optic nerve hypoplasia (CONH) were reviewed. It was found that the risk of having an affected child is higher in an adolescent mother, and that maternal alcohol or drug abuse may be important factors. Frequently the disorder is associated with other neuropsychiatric handicaps, and with neuro-endocrine abnormalities. The findings suggest that CONH probably is not a homogeneous group of disorders; some may be caused by primary failure of differentiation of the retinal ganglion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The most prominent and consistently reported prenatal features of ONH are young maternal age and primiparity [1822]. Many reports speculate that the association of young maternal age reflects an increased risk of unhealthy behavior and poor preconceptual health.…”
Section: Etiologic Correlatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prominent and consistently reported prenatal features of ONH are young maternal age and primiparity [1822]. Many reports speculate that the association of young maternal age reflects an increased risk of unhealthy behavior and poor preconceptual health.…”
Section: Etiologic Correlatesmentioning
confidence: 99%
“…ONH has long been linked to recreational (e.g., LSD) or prescription (e.g., anticonvulsants, quinine, antidepressants) drugs [12, 18, 21, 2430], viral infection [18, 31, 32], maternal diabetes [33], and alcohol use [34, 35] during pregnancy. Nearly all of these suggested etiologic correlates arose primarily from isolated exposures or case reports, providing the lowest level of evidence.…”
Section: Etiologic Correlatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective review of patients with optic nerve hypoplasia [13] found that 6 of 51 children (12%) had experienced NH (< 1.38 mmol/L for preterm and < 1.94 mmol/L for full term babies). However, a larger prospective study of optic nerve hypoplasia revealed that only 5 of 93 (5%) children with optic nerve hypoplasia had experienced NH [14].…”
Section: Neonatal Hypoglycaemia and Ocular Developmentmentioning
confidence: 99%
“…Optic nerve hypoplasia (ONH), a developmental abnormality of the optic nerves, is one of the leading causes of VI in the developed world, with a prevalence of 10.9 per 100,000 in England (2006) [4]–[6]. Children with severe or profound VI and isolated ONH are diagnosed with behavioral and developmental abnormalities at a similar rate to children with septo-optic dysplasia (SOD), who have other midline brain and/or pituitary hormone abnormalities in addition to ONH [7], [8]. However, the prevalence of behavioral difficulties in children with mild to moderate or no VI and ONH has not previously been recorded in the literature.…”
Section: Introductionmentioning
confidence: 99%